القيم الحوارية والجوانب العقدية من مجادلات مؤمن آل فرعون - بلخيرات, زياد; جفال, يزيد; بكاكرة, بوبكر (جامعة الوادي university of eloued, 2018)
تناولنا في دراستنا هذه مجادلات مؤمن آل فرعون ، والتي ورد ذكرها في القرآن الكريم في سورة غافر ،حيث سلطنا الضوء على الجوانب العقدية التي اعتمدها هذا المؤمن في محاججة قومه من خلال ما قاله المفسرون ،ثم عرجنا إلى تفصيل منهجه وأسلوبه في حواره مع قومه ،وذلك من خلال عرض أساليب دعوته المختلفة ،حيث بدأ بدفاعه عن موسى عليه السلام بتلطف وحذر في أول الأمر ثم بصراحة وظهور في النهاية ،وعرضه في جداله مع فرعون حجج الحق وبراهينه القوية الناصعة ، محذرا إياهم يوم القيامة ،ممثلا لهم بعض المشاهد في أسلوب مؤثر مذكرا إياهم بموقفهم وموقف الأجيال قبلهم؛ من يوسف عليه السلام ورسالته ،انتهاء بعرض مآل المؤمن ونجاته ،وعاقبة قومه ،ثم ذكرنا بعض الفوائد والعبر من هذه المجادلات ،ثم أنهينا البحث بخاتمة تضمنت أهم النتائج المستخلصة.In this study, we discussed the arguments of the believer of Pharaoh, which was mentioned in the Quran in Surat Ghafer, where he highlighted the doctrinal aspects adopted by this believer in the argument of his people through the commentators, Then we discussed the details of his method and style in his dialogue with his people, His different calling styles Where he appeared in his defense of Moses peace be upon him first and foremost. Then frankly and finally appeared and presented in his argument with Pharaoh arguments and proof of strong and spotless, warning them on the Day of Resurrection as the representative of them some scenes in an influential style, reminding them of their position and the attitude of the generations before them of Yusuf peace be upon him and his message, and ended the presentation of the money of the insured and his survival and the consequences of his people, We also mentioned some benefits and lessons of these arguments.
عقيدة